Toolkit for Gender Inclusive Mobility Planning - (:unkn) unknown (Deutsches Institut für Urbanistik (Difu), 2026)
Women and gender minorities make up more than half the world's population, yet transportation systems have historically been planned around a default male user. Research indicates that women and gender minorities navigate mobility networks differently, yet their travel patterns and needs remain underserved by conventional planning models. By prioritizing the needs of women and gender minorities, planners can design safer and more accessible transportation systems that enhance the experience for every user. This toolkit offers practical resources and guidance for designers, planners, and policymakers looking to integrate gender-inclusive practices into mobility and transportation planning. Mirroring the key phases of the urban planning process, the toolkit features chapters on topics such as data collection and public participation, each illustrated by a case study from local government projects. The toolkit also includes a Practitioner's Guide that highlights key points and recommendations, allowing readers to quickly grasp and apply key guidance without reading the entire toolkit. While the toolkit is not comprehensive, it offers a starting point for re-examining and improving transportation and mobility systems at the local level.
Best practices and case studies for urban planners and designers
Keywords: Gender; Mobilität; Inklusion; Verkehrsplanung